ASSOCIATION BETWEEN CHARACTERISTICS OF PHYSICAL ACTIVITY ACCUMULATION AND MORTALITY RISK. (11th November 2018) - Wanigatunga, A; Di, J; Zipunnikov, V; Kuo, P; Urbanek, J; Simonsick, E M; Schrack, J A
Abstract: Deteriorating physical activity (PA) accumulation may be an indicator of premature mortality. In 698 older adults, Cox proportional hazard models were fitted to determine the interaction effect between age and three different PA metrics (total PA minutes; fragmentation defined as the # contiguous PA minutes (bouts)/total PA minutes; and proportion of time spent in <5 and ≥10 minute bouts of total PA) on mortality risk. With increasing age, greater total PA (HR:0.97, 95% CI:0.95–0.99) and lower fragmentation (HR:0.97, 95% CI:0.94–0.99) were negatively associated with mortality risk. Proportion of PA spent in <5 minute bouts (HR:1.03, 95% CI:1.01–1.05) was positively associated with mortality risk while the proportion in ≥10 minute bouts (HR:0.98, 95% CI:0.96–1.00) was negatively associated with mortality risk. Our results suggest that fragmented accumulation of PA is associated with greater mortality risk in older adults. Conversely, PA accumulated in bouts lasting 10+ minutes appeared to provide a mortality benefit.